2018
DOI: 10.1093/humrep/dey044
|View full text |Cite
|
Sign up to set email alerts
|

Live birth rates in the first complete IVF cycle among 20 687 women using a freeze-all strategy

Abstract: This work was supported by grants from the National Natural Science Foundation of China (NSFC) (31770989 to Y.W.) and the Shanghai Ninth People's Hospital Foundation of China (JYLJ030 to Y.W.). None of the authors have any conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 19 publications
1
61
3
1
Order By: Relevance
“…This phenomenon can be explained by a possible asynchrony between the embryo and the endometrium, a fact that was not detected in egg‐donor cycles or embryo thaw cycles (Richter, Shipley, McVearry, Tucker, & Widra, ; Shapiro, Daneshmand, Garner, Aguirre, & Ross, ). Such evidence has led to the practice of cryopreservation of all oocytes or embryos of the cohort and transfer in a subsequent cycle, free of the action of gonadotrophins, the so‐called freeze‐all policy (Chang et al, ; Roque, ; Roque, Valle, Guimaraes, Sampaio, & Geber, ), with the possibility of leading to superior results (Braga et al, ; Chang et al, ; Magdi et al, ; Roque, ; Roque et al, ; Roque, Valle, Guimaraes, Sampaio, & Geber, ; Shapiro, Daneshmand, Garner, Aguirre, & Hudson, ; Zhu et al, ). In addition, the freeze‐all policy allows the personalized embryo transfer, at the defined moment of the WOI and the stage of development of the embryo, after access to the stage of endometrial development.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon can be explained by a possible asynchrony between the embryo and the endometrium, a fact that was not detected in egg‐donor cycles or embryo thaw cycles (Richter, Shipley, McVearry, Tucker, & Widra, ; Shapiro, Daneshmand, Garner, Aguirre, & Ross, ). Such evidence has led to the practice of cryopreservation of all oocytes or embryos of the cohort and transfer in a subsequent cycle, free of the action of gonadotrophins, the so‐called freeze‐all policy (Chang et al, ; Roque, ; Roque, Valle, Guimaraes, Sampaio, & Geber, ), with the possibility of leading to superior results (Braga et al, ; Chang et al, ; Magdi et al, ; Roque, ; Roque et al, ; Roque, Valle, Guimaraes, Sampaio, & Geber, ; Shapiro, Daneshmand, Garner, Aguirre, & Hudson, ; Zhu et al, ). In addition, the freeze‐all policy allows the personalized embryo transfer, at the defined moment of the WOI and the stage of development of the embryo, after access to the stage of endometrial development.…”
Section: Discussionmentioning
confidence: 99%
“…To further improve IVF outcomes, it has been suggested to freeze all the embryos obtained in a stimulation cycle and then plan a deferred transfer during a natural cycle or with hormone replacement with exogenous estradiol (E2) and progesterone (P) for endometrial priming [105,106]. With this strategy, the frozen-thawed embryos are transferred into a more "physiological milieu" which seems to improve implantation and outcomes compared to fresh transfer [106][107][108].…”
Section: Future Perspective: the Freeze-all Strategymentioning
confidence: 99%
“…A recent retrospective study using the general population has reported that 50.74% of patients using the freeze-all strategy achieved a live birth after the first complete cycle [105]. Additionally, another study indicated positive results in poor ovarian responders, and suggested the freeze-all strategy as an alternative to cycle cancellation for these patients [110].…”
Section: Future Perspective: the Freeze-all Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first live birth conceived using frozen‐thawed embryos three decades ago (Trounson & Mohr, ), significant progress has been made in the cryopreservation techniques used in assisted reproductive technology (ART). The switch from slow programmed frozen methods to current vitrification methods has greatly improved ART efficiency (Zhu et al, ). Thus, freezing embryos has become a routine practice for ART units, and some units have recently even started to use the “freeze‐all” strategy for certain patients (Bhattacharya, ; Roque, Valle, Sampaio, & Geber, ).…”
Section: Introductionmentioning
confidence: 99%